2008
DOI: 10.1143/jjap.47.6007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electron Beam Recorder for Mastering of Future Storage Media

Abstract: We construct a new class of scalar noncommutative multi-solitons on an arbitrary Kähler manifold by using Berezin's geometric approach to quantization and its generalization to deformation quantization. We analyze the stability condition which arises from the leading 1/ correction to the soliton energy and for homogeneous Kähler manifolds obtain that the stable solitons are given in terms of generalized coherent states. We apply this general formalism to a number of examples, which include the sphere, hyperbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The electron optics are composed of a three-lens system designed to achieve a small beam size with a high current. 9) We evaluated the beam convergence characteristic using the beam size measurement method of BEAMETR 13) (Abeam Technologies). Figure 5 shows the results measured at a beam current of 30 nA.…”
Section: Electron Beam Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron optics are composed of a three-lens system designed to achieve a small beam size with a high current. 9) We evaluated the beam convergence characteristic using the beam size measurement method of BEAMETR 13) (Abeam Technologies). Figure 5 shows the results measured at a beam current of 30 nA.…”
Section: Electron Beam Columnmentioning
confidence: 99%
“…We have been developing electron beam recorders (EBRs) since 1993 and have reported their ability of high-density mastering for storage media. [4][5][6][7][8][9] EBR is an EB lithography system with an r-stage, which is well suited for generating concentric (or spiral) patterns with high resolution such as patterned media. In particular, EBR has significant advantages in throughput and stitching accuracy over conventional EB lithography systems with an X-Y stage.…”
Section: Introductionmentioning
confidence: 99%
“…Heidler et al [5] designed a twostage exhaust seal system and experimentally confirmed that the designed vacuum-compatible aerostatic guide could maintain a vacuum level of the order of 10 −4 Pa during the experiment. Wada et al [6,7] conducted electron beam machining using a vacuumcompatible aerostatic spindle for next-generation high-density optical discs in vacuum, and they reported that 12 nm-wide grooves could be formed on a wafer surface. However, vacuum-compatible aerostatic bearings need a multistage seal system that consists of several viscous seals, exhaust tubes and vacuum pumps to maintain a high degree of vacuum in a chamber, and therefore, this seal system is very complicated and requires large amounts of space for seal regions and tubing.…”
Section: Introductionmentioning
confidence: 99%